1998
DOI: 10.1038/sj.bjc.6690020
|View full text |Cite
|
Sign up to set email alerts
|

Combination oral antiangiogenic therapy with thalidomide and sulindac inhibits tumour growth in rabbits

Abstract: Neovascularization facilitates tumour growth and metastasis formation. In our laboratory, we attempt to identify clinically available oral efficacious drugs for antiangiogenic activity. Here, we report which non-steroidal anti-inflammatory drugs (NSAIDs) can inhibit corneal neovascularization, induced by basic fibroblast growth factor (bFGF) or vascular endothelial growth factor (VEGF). This antiangiogenic activity may contribute to the known effects of NSAIDs on gastric ulcers, polyps and tumours. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…Our study on preclinical trial addresses the efficiency of thalidomide in lung adenocarcinoma, a subtype of non -small cell lung cancer. Several studies have reported that thalidomide reduces vascular endothelial growth factor expression in tumor tissues, leading to a dramatic decrease in vascular density and permeability, and an increase in tumor cell apoptosis (38). Our results also showed that thalidomide inhibits the overexpression of vascular endothelial growth factor in tumors excised from nude mice.…”
Section: Discussionsupporting
confidence: 73%
“…Our study on preclinical trial addresses the efficiency of thalidomide in lung adenocarcinoma, a subtype of non -small cell lung cancer. Several studies have reported that thalidomide reduces vascular endothelial growth factor expression in tumor tissues, leading to a dramatic decrease in vascular density and permeability, and an increase in tumor cell apoptosis (38). Our results also showed that thalidomide inhibits the overexpression of vascular endothelial growth factor in tumors excised from nude mice.…”
Section: Discussionsupporting
confidence: 73%
“…These observations concur with reports that in mice, thalidomide is not teratogenic, 30 is unable to oxidize DNA, 18,31 and has no antitumor nor antiangiogenic effects in mice bearing several types of tumors. [32][33][34] Others reported that thalidomide had an antiangiogenic effect in V2 carcinoma growing in rabbits, 29 but that human or rabbit microsomes were required for in vitro inhibition of microvessel formation in a rat aorta system and for inhibiting proliferation of human aortic endothelial cells by thalidomide, 26 supporting the notion that active metabolites of thalidomide are responsible, at least in part, for its antiangiogenic properties. None of these studies reports measurement of thalidomide metabolism or the presence of its metabolites.…”
Section: Discussionmentioning
confidence: 61%
“…It also reduces tumor necrosis factor-alpha (TNF-α) production by monocytes and macrophages. Animal models demonstrated thalidomide activity against solid tumors in rabbits and nude mice, and it produced apoptosis in established tumors [22][23]. Singhal and colleagues were among the first to report significant activity of thalidomide in a population of patients with advanced, previously treated multiple myeloma [11].…”
Section: Discussionmentioning
confidence: 99%